2014
DOI: 10.1111/roie.12152
|View full text |Cite
|
Sign up to set email alerts
|

The Border Effect and the Nonlinear Relationship between Trade and Distance

Abstract: After the seminal paper by McCallum, various authors have estimated the effect of regional and national borders on trade. This paper digs deeper into the matter, estimating how the internal and external border effect is affected by the non-linear relation between trade and distance at different spatial levels, and the econometric procedure used to control for it. Our paper uses a novel dataset that captures intra-and inter-national truck shipments between Spanish regions and regions in eight European countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 76 publications
1
13
0
Order By: Relevance
“…Other authors have also found significant border effects (Daumal & Zignago, ; Gallego & Llano, ). As a result of this, we follow Gallego and Llano () to control for trade flows between contiguous regions using dummy variables. Controlling for trade flows partially corrupted due to using parameterised estimations is a concern when working with regional trade databases to avoid flawed results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have also found significant border effects (Daumal & Zignago, ; Gallego & Llano, ). As a result of this, we follow Gallego and Llano () to control for trade flows between contiguous regions using dummy variables. Controlling for trade flows partially corrupted due to using parameterised estimations is a concern when working with regional trade databases to avoid flawed results.…”
Section: Methodsmentioning
confidence: 99%
“…Departing from this scarcity of data, different authors have estimated regional trade performance in Europe using the C-intereg database. These studies, however, are mainly devoted to studying the impact of port facilities on trade (Alama et al, 2013(Alama et al, , 2015Márquez-Ramos, 2016) or the border impediments to trade (Gallego & Llano, 2014, 2015. Bensassi et al (2015) study the effect of broadband on trade at regional level.…”
Section: Further Research: Empirical Evidence About the Role Of Regmentioning
confidence: 99%
“…The differential result ascribed to the presence of a border has been recently (Gallego and Llano, 2014) connected to the non-linear relationship between trade and distance. As suggested by Hillberry and Hummels (2008), spatial frictions matter and have the greatest effect on very short distances rather than longer ones.…”
Section: Distance Borders Proximity and Tradementioning
confidence: 99%
“…The value of spline regression models has been emphasised through a significant amount of previous work. Particularly, many earlier studies in applied economics (Berberoğlu, 2012;Budiantra, Ratna, Zain, & Wibowo, 2012;Gallego & Llano, 2014;Greiner & Kauermann, 2007, 2008Horowitz, Loughran, & Savin, 2000;Hwang & Wu, 2011;Kuepie, Nordman, & Roubaud, 2009;Martín-Rodríguez & Cáceres-Hernández, 2005a, 2005b, 2012Osinubi & Olaleru, 2006;Sarvida & Baguio, 2010;Sing, 2010;Williams, 2009;Yang & Song, 2014) frequently used spline regression models and functions when analysing time series data.…”
Section: Introductionmentioning
confidence: 99%